Curcumin and its analogues protect from endoplasmic reticulum stress: Mechanisms and pathways. (August 2019) - Shakeri, Abolfazl; Zirak, Mohammad Reza; Wallace Hayes, A.; Reiter, Russel; Karimi, Gholamreza
Graphical abstract: Abstract: The endoplasmic reticulum (ER), a cellular organelle with multiple functions, plays an important role in several biological processes including protein folding, secretion, lipid biosynthesis, calcium homeostasis, and cellular stress. Accumulation of misfolded or unfolded proteins in the ER makes cells undergo a stress response known as the unfolded protein response (UPR). UPR is initially protective. However, prolonged and severe ER stress can lead to autophagy and/or the induction of apoptosis in stressed cell. Many studies have demonstrated that ER stress and the UPR are involved in different diseases such as neurodegenerative diseases, cancer, osteoporosis, diabetes, and inflammatory diseases. Curcumin, a natural polyphenol, has well documented evidence supporting its numerous biological properties including antioxidant, anti-inﬂammatory, immune-modulatory, anti-microbial, anti-ischemic, anti-angiogenesis, neuroprotective, hepatoprotective, nephroprotective, anti-atherogenic and anti-diabetic activities. In this review, the role of ER stress in several pathological condition and the potential protective effects of curcumin are discussed.